Reliability of the Fenton growth curve method in predicting birth weight in newborns born at or before 36 weeks gestational age - Gungor, Sara; Hou, Wei; Decristofaro, Joseph; Maduekwe, Echezona T. (Frontiers in Pediatrics, 2025)
ObjectivesThe study aimed to assess the reliability of the Fenton curve superimposed with fetal weight percentile in predicting the birth weight of infants born ≤36 weeks gestational age.Study designThis prospective observational study, conducted from December 2018 to May 2019, examined infants born ≤36 weeks gestational age. The Fenton curve was used to extrapolate the fetal growth percentile (Fenton curve method) and predict the birth weight of the infants on the day of delivery. The study excluded infants who were large or small for gestational age and those diagnosed with congenital anomalies or Hydrops fetalis. The Fenton curve method was used to predict the actual birth weight of 65 infants born at Stony Brook University Hospital and was compared with their actual birth weight using a two-sample t-test and Bland–Altman test.ResultsThe study enrolled 65 infants, including 37 females, 2 Asians, 6 Blacks, 17 Hispanics, and 40 whites, with a mean gestational age of 32.1 ± 3.6 weeks and a mean actual birth weight of 1,860 ± 677 grams. The results showed no significant difference between the predicted and actual birth weight (p = 0.17), with a median difference of 32.2 grams between the predicted and actual weight.ConclusionThe study found that the Fenton curve method reliably predicted the birth weight of infants born ≤36 weeks of gestational age. The results indicate that in normally grown fetuses, healthcare providers in the delivery room could potentially use Fenton curve predicted birth weight for drug dosage and equipment sizing in scenarios where obtaining actual birth weight is not possible. Nonetheless, additional analysis in larger cohorts is needed before this method can be universally adopted.